As várias faces do cuidar de si - Fuentes, Sônia Azevedo Menezes Prata Silva (2011)
The objective of the present work is to understand the vision that the professionals have about the meanings of self care, considering that the subjects interviewed for this dissertation are people that work, research, and/or study the question of the ageing process. Consequently to that question, I examined proposals suggested in the sense of raising alternatives and reflections about the quality of life and special cares, for those individuals that are part of the elderly segment. For this I interviewed ten professionals of significant relevance in the area, that either study or work with the ageing process, Five questions were asked to the subjects with the intention to understand each one's personal visions about: self care, the difference between self care while young and self care for the elderly, to know what is important for the person being interviewed, to take care beyond the physical body; to see if the person interviewed realizes the importance of taking care of himself, and finally what do they consider important to build a prevention program considering self care. I established in this research dialogues between the thoughts of several authors as Foucault, Freud, Melaine Klein, Jung, Winnicott, Mucida, Ayres, Birman, Carielo, Medeiros, Debert, Goldfarb, Martins, and others